Outcomes of Chronic Hemodialysis Patients in the Intensive Care Unit - Melanie Chan; Marlies Ostermann (Critical Care Research and Practice)
Patients with end-stage renal disease (ESRD) experience higher rates of hospitalisation, cardiovascular events, and all-cause mortality and are more likely to require admission to the intensive care unit (ICU) than patients with normal renal function. Sepsis and cardiovascular diseases are the most common reasons for ICU admission. ICU mortality rates in patients requiring chronic hemodialysis are significantly higher than for patients without ESRD; however, dialysis patients have a better ICU outcome than those with acute kidney injury (AKI) requiring renal replacement therapy suggesting that factors other than loss of renal function contribute to their prognosis. Current evidence suggests, the longer-term outcomes after discharge from ICU may be favourable and that long-term dependence on dialysis should not prejudice against prompt referral or admission to ICU.